PENGARUH PENDIDIKAN ISLAM TERHADAP PERKEMBANGAN EMOSIONAL ANAK: PERSPEKTIF PSIKOLOGI PENDIDIKAN DALAM KELUARGA DAN SEKOLAH - Muhamad Ishaac; Muhammad Ferdy Hidayat; M. Zaki Mubarak (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
This study examines the role that Islamic education plays in the emotional development of children, particularly through family and school environments. The purpose of this study is to investigate how Islamic principles, such as kesabaran, kejujuran, and kasih sayang, can improve children's emotional stability and strengthen Islamic character. Using a pustaka method and a kualitatif approach, this study analyzes many academic topics related to Islamic education and perkembangan psychology. The results indicate that Islamic education that is integrated into families and schools helps children develop empathy, increase their level of patience, and build positive social relationships. Islamic-based education does more than just help children develop their emotional intelligence; it also teaches them how to deal with social pressures in a responsible and efficient manner. Accordingly, this study highlights the importance of teaching children the principles of Islam as a means of fostering their development. Keywords:  Islamic education; emotional development; Islamic character; early childhood; educational psychology